Size Effects in Sodium Ion Batteries. (23rd September 2021) - Zhang, Zhibo; Wang, Ruize; Zeng, Jinquan; Shi, Kaiyuan; Zhu, Changbao; Yan, Xingbin
Abstract: Sodium ion batteries (SIBs) are promising candidates for large‐scale energy storage owing to the abundant sodium resources and low cost. The larger Na + radius (compared to Li + ) usually leads to sluggish reaction kinetics and huge volume expansion. One of the efficient strategies is to reduce the size of electrode materials or the components of electrolytes to a suitable scale where size effect begin to emerge, leading to the improved or varied thermodynamics, kinetics, and mechanisms of sodium storage. However, only a few systematic reviews address size effects in SIBs, which requires further attention urgently. Herein, after a brief discussion of the general size effect, the size‐related kinetics, thermodynamics (equilibrium voltage and morphology), and sodium storage mechanisms (phase transition, conversion reaction, interfacial, and nanopore storage) of electrode materials are presented. The size effect on liquid, polymer, and inorganic solid‐state electrolytes are discussed as well, including the size of solvent molecules, Na salts, and inorganic fillers. Finally, neutral and adverse size effects are discussed, and some useful strategies are proposed to overcome them. The deep insights into the size effect will provide instructive guidelines for developing SIBs and other new energy storage systems. Abstract : In this review, the size effects and their influences on electrodes (the kinetics, thermodynamics and sodium storage mechanisms) and electrolytes (the liquid electrolytes, polymer electrolytes and solid‐state inorganic electrolytes) in sodium ion batteries are summarized and discussed systematically.